ISOLATION AND FUNCTIONAL CHARACTERISATION OF ENDOPHYTIC BACTERIAL ISOLATES FROM CURCUMA LONGA - NEETHU SAHADEVAN; VISHNUPRIYA. S; JYOTHIS MATHEW (International Journal of Pharma and Bio Sciences, 2016)
Endophytes are unique group of microorganisms residing within the specific chemical environment of host plants. Medicinal plants can have potential and diverse microbial association. The rhizome of turmeric is very remarkable due to its metabolite richness and the physiological processes associated with these tissues. But the functional role of endophytic microorganisms in this tissues remain totally unexplored. In the present study two endophytic bacterial isolates, Alcaligenes faecalis and Enterobacter sp were found to have the ability to produce IAA, ACC deaminase, phosphate solubilisation and to fix atmospheric nitrogen. By considering these plant growth promoting properties, Alcaligenes faecalis and Enterobacter sp can expect to have considerable effect on the growth of turmeric.